Open innovation as a possibility of diversification of cooperation agents with the innovation processes in the garment industry (ModaPalavra e-periódico, 2015)
Innovation has different management models that value internal and external sources of knowledge. When considering these aspects, this research presents the open innovation model, aiming at the description of their practices and relating them to the innovation process in the garment, apparel or clothing industries. For that an unsystematic literature review in order to understand the concepts inherentin the theme of the research was conducted. Finally, the authors concluded that the different open innovation practices are applicable in the clothing sector, which enables the establishment of partnerships with various institutions, increasing the competitiveness indices and reducing the risks promoted by high investments.
Keywords: open innovation; garment industry; cooperation